2015
DOI: 10.1158/2159-8290.cd-13-1050
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CHK1 by ETS Family Members Promotes DNA Damage Response Bypass and Tumorigenesis

Abstract: The ETS family of transcription factors has been repeatedly implicated in tumorigenesis. In prostate cancer, ETS family members such as ERG, ETV1, ETV4 and ETV5 are frequently overexpressed due to chromosomal translocations, but the molecular mechanisms by which they promote prostate tumorigenesis remain largely undefined. Here we show that ETS family members such as ERG and ETV1 directly repress the expression of the checkpoint kinase 1 (CHK1), a key DNA Damage Response (DDR) cell cycle regulator essential fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…Consistent with the previous reports, 21, 22 we observed a relatively high basal level of γ -H2Ax foci and spontaneous apoptosis in VCaP cells, reflecting DNA damage caused by ERG upregulation. Notably, at 50 nM, MLN slightly decreased the incidence of γ -H2AX foci, implying that the G0/G1 cell cycle arrest and reduced rate of DNA synthesis induced at this dose prevented spontaneous DNA breaks.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with the previous reports, 21, 22 we observed a relatively high basal level of γ -H2Ax foci and spontaneous apoptosis in VCaP cells, reflecting DNA damage caused by ERG upregulation. Notably, at 50 nM, MLN slightly decreased the incidence of γ -H2AX foci, implying that the G0/G1 cell cycle arrest and reduced rate of DNA synthesis induced at this dose prevented spontaneous DNA breaks.…”
Section: Resultssupporting
confidence: 93%
“…The proportion of cells in S-phase at 24 h following the IR and PARPi combination treatment was 2-fold greater in TMPRSS2-ERG compared to parental PC3 cells. These data could partially explain the increased radiosensitivity of TMPRSS2-ERG-positive cells with PARPi treatment (13), as cell cycle arrest due to checkpoint activation after IR was reduced in the presence of TMPRSS2-ERG compared to PC3 parental cells, as recently reported (33), yet PARP inhibition compensated for this reduction.…”
Section: Resultssupporting
confidence: 60%
“…A recent report has shown that ERG directly represses the expression of the checkpoint kinase 1 (CHK1), a key DNA damage response cell cycle regulator that is essential for the maintenance of genome integrity. This study found that ERG expression correlates with CHK1 downregulation in human patients and that CHK1 downregulation sensitized PCa cells to DNA-damage (etoposide) but not docetaxel-based treatment (33). This finding provides support for the cell cycle differences we observed in the TMPRSS2-ERG-expressing cells.…”
Section: Discussionmentioning
confidence: 76%
“…Even more strikingly, the genes of several key signaling factors (PAK1, CREM) and of the epigenetic modulator SMARCD3 have apparently acquired ERG binding capability in their promoter regions during tumorigenesis (for SMARCC1, see Extended Data Fig. 4c), as it was reported for the ERG-mediated repression of checkpoint kinase 1 31 . In contrast, P6 showed a very small number of deregulated components of the core Wnt pathway (Fig.…”
mentioning
confidence: 63%